Retrospective Evaluation of Bayesian Risk Models of LVAD Mortality at a Single Implant Center - Lohmueller, Lisa C.; Kanwar, Manreet K.; Bailey, Stephen; Murali, Srinivas; Antaki, James F. (Frontiers in Medicine, 2018)
Use of a left ventricular assist device (LVAD) can benefit patients with end stage heart failure, but only with careful patient selection. In this study, previously derived Bayesian network models for predicting LVAD patient mortality at 1, 3, and 12 months post-implant were evaluated on retrospective data from a single implant center. The models performed well at all three time points, with a receiver operating characteristic area under the curve (ROC AUC) of 78, 76, and 75%, respectively. This evaluation of model performance verifies the utility of these models in “real life” scenarios at an individual institution.